2003
DOI: 10.1159/000073750
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of the Mitosis-Promoting Factor in Postmitotic Cardiomyocytes

Abstract: Cardiomyocytes cease to divide shortly after birth and an irreversible cell cycle arrest is evident accompanied by the downregulation of cyclin-dependent kinase activities. To get a better understanding of the cardiac cell cycle and its regulation, the effect of functional recovery of the mitosis-promoting factor (MPF) consisting of cyclin B1 and the cyclin-dependent kinase Cdc2 was assessed in primary cultures of postmitotic ventricular adult rat cardiomyocytes (ARC). Gene transfer into ARC was achieved using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Furthermore, cyclin A2 induced cardiomyocyte mitosis (H3P), increased myocardial proliferation, and improved heart function after MI, 19,20 while ectopic expression of cyclin B1 and Cdk2 induced mitosis-promoting factor (MPF) activity in adult cardiomyocytes, which resulted in a mitotic phenotype, but no complete cell division. 21 Taken together, the data in the current study further confirm that manipulation of cell cycle regulation might offer reasonable strategies for cardiac regeneration and treatment of ischaemic heart failure. The significance of the induced myocyte proliferation is strengthened by the observed protection against cardiac dysfunction and heart failure in an ischaemia/reperfusion-induced acute MI model.…”
supporting
confidence: 76%
“…Furthermore, cyclin A2 induced cardiomyocyte mitosis (H3P), increased myocardial proliferation, and improved heart function after MI, 19,20 while ectopic expression of cyclin B1 and Cdk2 induced mitosis-promoting factor (MPF) activity in adult cardiomyocytes, which resulted in a mitotic phenotype, but no complete cell division. 21 Taken together, the data in the current study further confirm that manipulation of cell cycle regulation might offer reasonable strategies for cardiac regeneration and treatment of ischaemic heart failure. The significance of the induced myocyte proliferation is strengthened by the observed protection against cardiac dysfunction and heart failure in an ischaemia/reperfusion-induced acute MI model.…”
supporting
confidence: 76%
“…S2, D -F). Interestingly, once the nuclear membrane Several studies have shown that manipulation of cell cycle proteins can induce NRVCs to reenter the cell cycle (e.g., Agah et al, 1997 ;Huh et al, 2001 ;Datwyler et al, 2003 ;Tamamori-Adachi et al, 2003 ;Engel et al, 2005 ;Jung et al, 2005 ;Tseng et al, 2006 ). These studies used reagents (e.g., BrdU incorporation or Ki67 immunostaining) that refl ect entry into the cell cycle or S phase but not entry into mitosis or cell division.…”
Section: Progression Through the Cell Cycle: Implications Of The Neonmentioning
confidence: 99%
“…S2, D -F). Interestingly, once the nuclear membrane Several studies have shown that manipulation of cell cycle proteins can induce NRVCs to reenter the cell cycle (e.g., Agah et al, 1997 ;Huh et al, 2001 ;Datwyler et al, 2003 ;TamamoriAdachi et al, 2003 ;Engel et al, 2005 ;Jung et al, 2005 ;Tseng et al, 2006 ). These studies used reagents (e.g., BrdU incorporation or Ki67 immunostaining) that refl ect entry into the cell cycle or S phase but not entry into mitosis or cell division.…”
Section: Progression Through the Cell Cycle: Implications Of The Neonmentioning
confidence: 99%